Economic and Environmental Benefits of Using Waste Potential as a Valuable Secondary and Energy Resource - BEREZYUK, Sergiy; TOKARCHUK, Dina; PRYSHLIAK, Natalia (Journal of Environmental Management and Tourism, 2019)
The article is devoted to solving the problems of recycling in Ukraine, as the accumulation of waste every year becomes more and more threatening. Waste accumulated in landfills occupies 7 percent of the territory of Ukraine (more than 43 thousand km 2 ), which simultaneously leads to pollution of water, soil, air and the deterioration of the ecological and economic situation in general. The experience of European countries in dealing with waste indicates the complexity and effectiveness of measures for their effective management, which is not currently available in Ukraine. The main objective of the article is to provide proposals on improving the processes of safe waste management in Ukraine, taking into account the EU experience and identifying a number of measures that will facilitate the effective management of solid household waste in Ukraine. The object of the research is municipal solid waste as a source of valuable secondary raw materials, as well as an energy resource. The research methodology includes the application of the dialectical approach and the methods of economic analysis: abstract-logical, statistical-economic, tabular and graphic, monographic, economic-mathematical (extrapolation method). The article highlights the ecological and energy efficiency of the secondary use of a valuable resource of solid household wastes. A scheme for organizing the effective utilization of solid household waste is proposed, the implementation of which is of practical importance in the implementation both at the level of individual communities and the state as a whole.